Between Object and Idea: Non-Normative Dress in the Roman Republic - Kaczmarek, Zofia (Sensus Historiae, 2025)
From its beginning dress has been a cover of human nakedness, a barrier between the human body and the unfriendly outside world. In the meantime, it evolved to be a sign of human status, gender, origin, etc. Thus, there are two worlds of dress: the tangible and the elusive one, the world in which dress is an object and the world in which it is an idea. People tried to subdue the first one, but they never gained full control over the other. That is why in highly hierarchical societies, such as the one of Ancient Rome, dress was one of the most important status guardians and a means of negotiation. In this paper, I introduce the idea ofnon-normative dress and the methods of studying it in the society of the Roman Republic.